Leishmania (Viannia) lainsoni (Kinetoplastida: Trypanosomatidae), a divergent Leishmania of the Viannia subgenus: a mini review - José R Corrêa; Reginaldo P Brazil; Maurilio J Soares (Memorias do Instituto Oswaldo Cruz, 2005)
Leishmania (Viannia) lainsoni is the Leishmania species that presents the most distinct biological (morphology, growth in axenic culture medium), biochemical (enzymatic electrophoresis profile), and molecular biology characteristics, when compared to other species of the Viannia subgenus. Development of promastigote forms of this parasite attached to the wall of the pyloric and hind gut regions of sand fly vectors is a solid characteristic that allows its positioning in the Viannia subgenus. However, taxonomic data from biochemical and molecular techniques on this Leishmania species are still not conclusive. It is evident the difficulty in taxonomically positioning this borderline Leishmania species. In this review we present the data accumulated since L. (Viannia) lainsoni has been described and we discuss its position in the Viannia subgenus.